Homocystinuria: Diagnosis and Neuroimaging Findings - of Iranian Pediatric patients - KARIMZADEH, Parvaneh; JAFARI*, Narjes; ALAI, Mohammad Reza; JABBEHDARI, Sayena; NEJAD BIGLARI, Habibeh (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Karimzadeh P, Jafari N, Alai MR, Jabbehdari S, Ahmad Abadi F, NejadBiglari H. Homocystinuria: Diagnosis and Neuroimaging Findings - of Iranian Pediatric Patients. Iran J Child Neurol. 2015 Winter;9(1):94-98. Abstract Objective Homocystinuria is a neurometabolic diseases characterized by symptoms include Neurodevelopmental delay, lens dislocation, long limbs and thrombosis. Materials & Methods The patients who were diagnosed as homocystinuria marfaniod habits, seizure in the Neurology Department of Mofid Children’s Hospital in Tehran, Iran between 2004 and 2014 were included in our study. The disorder was confirmed by clinical andneuroimaging findings along withneurometabolic and genetic assessment fromreference laboratory in Germany. We assessed age, gender, past medical history, developmental status, clinical manifestations, and neuroimaging findings of 20 patients with homocystinuria. Results A total of 75% of patients were offspring from consanguineous marriages. A total of 95% of patients had a history of developmental delay and 40% had developmental regression. A total of 75% had seizures from these 45% showed refractory seizures. Seizures among 13 patients werecontrolled with suitable homocystinuria treatment. The patients with homocystinuriawere followed for approximately 10 years and the follow-ups showed that the patients with an early diagnosis and treatment had more favorable clinical responses for growth index, controlled refractory seizures, neurodevelopmental status, and neuroimaging findings. Neuroimaging findings include brain atrophy and/or white matter involvement. Conclusion According to the results of this study, we suggest that early assessment and detectionplayan important role in the prevention of disease progression and clinical signs. Homocystinuria in patients with a positive family history, developmental delays, or regression, refractory, or recurrent seizures should take precedence over other causes. References Brustolin S1, Giugliani R, Félix TM. Genetics of homocystine metabolism and associated disorders.Braz J Med Biol Res. 2010 Jan; 43(1):1-7. Iacobazzi V, Infantino V, Castegna A, AndriaG. Hyperhomocysteinuria: Related genetic diseases and congenital defects, abnormal DNA methylation and newborn screening issues. Mol Genet Metab. 2014 September - October; 113(1-2):27-33. SelhubJ.Homocystinemetabolism.Annu Rev Nutr. 1999;19:217-46. Ali Z, Troncoso JC, Fowler DR.Recurrent cerebral venous thrombosis associated with heterozygote methylenetetrahydrofolate reductase C677T mutation and sickle cell trait without Homocysteinuria: An autopsy case report and review of literature.ForensicSci Int. 2014 Sep;242:e52-5. RozenR.Genetic modulation of Homocysteinuria. SeminThrombHemost. 2000;26(3):255-61. Palma Reis R, Sales Luis. Homocisteinemia e Doença Vascular – O Nascer de um Novo Factor de Risco. Rev Port Cardiol 1999; 18:507-14 McCully KS. Homocystine theory of arteriosclerosis: development and current status. Atherosclerosis Rev 1983;11:157-246. Malinow MR. Homocystinuria: a common and easily reversible risk factor for occlusive atherosclerosis. Circulation 1990;81:2004-6. Boushey CJ, Beresford SAA, Omenn GS, Motulsky AG. A quantitive assessment of plasma homocystine as a factor for vascular disease: probable benefits of increasing folic acid intakes. JAMA 1995;472:1049-57. Carson NAJ, Neill DW. Metabolic abnormalities detectedin a survey of mentally backward individuals in NorthernIreland. Arch Dis Child 1962;37:505-13. Gerritsen T, Waisman HA. Homocystinuria, an error inthe metabolism of methionine. Pediatrics 1964;33:413-20. Mallory T. Case records of the Massachusetts GeneralHospital.Case 19471. Marked cerebral symptoms followinga limp of three months duration. N Engl J Med 1933;209:1063-6. Shih VE, Efron ML. Pyridoxine-unresponsive homocystinuria. Final diagnosis of MGH case 19471. N Engl Med1970;283:1206-8. Kang SS, Wong PWK, Malinow MR. Hyperhomocyst(e) inemia as a risk factor for occlusive vascular disease.Ann Rev Nutr 1992;12:279-98. Mudd SH, Skovby F, Levey HL, et al. The natural history of homocystinuria due to cystathionine B-synthase deficiency. Am J Hum Genet 1985;37:1-31. Fonseca N1, Vidal N, Santos J, Brito AP, Bernardino L, Silvestre I, InêsL.Hyperhomocysteinuria–case report.Rev Port Cardiol. 2003 Feb;22(2):223-30. Mudd SH, Levy HL. Disorders of transsulfuration. InStanbury JB, Wingarden JB, Fredrickson DS, Goldstein JL,Bronw MS (eds.). The Metabolic Basis of Inherited Disease.New York, McGraw-Hill 1983;522-559. Sachdeva V1, Mittal V, Pathengay A, Kekunnaya R, Gupta A, Rao BV.Isolated abducens nerve palsy with hyperhomocysteinuria: Association and outcomes.Indian J Ophthalmol. 2013 Oct;61(10):598-600.